2019
DOI: 10.1021/acs.iecr.9b04213
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Fenton Degradation of Carbofuran in Helical Tube Microreactor and Kinetic Modeling

Abstract: The photo-Fenton process is intensified for degradation of carbofuran by using a tubular microreactor coiled around a florescent light. The microreactor attained 7.5 times faster degradation rate compared to a batch reactor operated under a LED light. At the initial Fe 2+ concentration of 0.25 mM, the degradation rates in the batch reactor were fast at first, subsequently became slow, and afterward gradually increased with time regardless of light intensity. In the microreactor, the degradation rates appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…If we disregard this concern, the consequences of this illegal loop in a mass-action mechanism can be explored by performing simulations of the loop based on the mechanism and parameters of a publication by Lin and Gurol 1998. 176 17,21,23,26,33,95,99,133,[176][177][178][179][182][183][184]187,189,190,193,195,197,198,200,203,204,206,207,211,218,219,[223][224][225]228 One of these shows the steps in the loop but then excludes them from the final model. 200 There are a few publications that use the inverse acid dependence in the first step of the loop (non-mass-action kinetics).…”
Section: Illegal Loops Not Involving Peroxo-fe Complexesmentioning
confidence: 99%
“…If we disregard this concern, the consequences of this illegal loop in a mass-action mechanism can be explored by performing simulations of the loop based on the mechanism and parameters of a publication by Lin and Gurol 1998. 176 17,21,23,26,33,95,99,133,[176][177][178][179][182][183][184]187,189,190,193,195,197,198,200,203,204,206,207,211,218,219,[223][224][225]228 One of these shows the steps in the loop but then excludes them from the final model. 200 There are a few publications that use the inverse acid dependence in the first step of the loop (non-mass-action kinetics).…”
Section: Illegal Loops Not Involving Peroxo-fe Complexesmentioning
confidence: 99%
“…A kinetic investigation of photo-Fenton processes in a microreactor has been presented very recently [54]. In this work, the adopted experimental set-up is of the same type as the one independently used for UVC/H 2 O 2 investigations, but with some substantial differences.…”
Section: Modeling For Photo-fenton Processesmentioning
confidence: 99%
“…Although some authors suggested the possibility of direct use of these devices for water treatment by numbering up units [25,42], this seems a fairly unrealistic and antieconomic scenario, with very few possible niche applications in the treatment of small volumes of water for specific applications. Only a limited number of papers have addressed the use of microreactors for the estimation of intrinsic parameters and mechanism identification, which can be used for the scale-up of AOPs for wastewater treatment, which, in fact, is the most promising application [9,11,12,23,[43][44][45][46][47][48][49][50][51][52][53][54]. In this sense, there is still extensive room for improvement and exploitation of this technology for the design and scale-up of such tertiary treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, more and more refractory organic pollutants resistant to traditional treatment methods have been found in water 1, 2 . Advanced oxidation processes (AOPs), such as Fenton, 3 catalytic ozonation, 4 persulfate, 5 and photocatalysis, 6 can efficiently destroy those refractory organic molecules through radicals with high oxidability. In addition to the single advanced oxidation technology, combined processes have received widespread attention in recent years due to their excellent treatment efficiency, e.g., photocatalytic ozonation 7–9 .…”
Section: Introductionmentioning
confidence: 99%